2013
DOI: 10.12681/mms.342
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds of some popular Mediterranean seafood species

Abstract: The volatile compounds of highly commercialised fresh Mediterranean seafood species, including seven fish (sand-smelt Atherina boyeri, picarel Spicara smaris, hake Merluccius merluccius, pilchard Sardina pilchardus, bogue Boobps boops, anchovy Engraulis encrasicolus and striped-mullet Mullus barbatus), squid (Loligo vulgaris), shrimp (Parapenaeus longirostris) and mussel (Mytilus galloprovincialis), were evaluated by simultaneous steam distillation-extraction and subsequent GC-MS analysis. A total of 298 volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Giogios et al . () evaluated the volatile compounds of the shrimp solution extracted via simultaneous steam distillation, and showed that the extract contained sulfur compounds and amines that impart a fishy odor. The highest preference scores, which reflected the property of shrimp‐like flavor, were given for the extracts and residues obtained at 160 and 180C.…”
Section: Resultsmentioning
confidence: 99%
“…Giogios et al . () evaluated the volatile compounds of the shrimp solution extracted via simultaneous steam distillation, and showed that the extract contained sulfur compounds and amines that impart a fishy odor. The highest preference scores, which reflected the property of shrimp‐like flavor, were given for the extracts and residues obtained at 160 and 180C.…”
Section: Resultsmentioning
confidence: 99%
“…in P. eryngii and P. ostreatus, respectively. Toluene derives from unsaturated fatty acids and has been reported in wild edible species [15], freeze-dried truffle (Tuber aestivum) [57], and other food items like cooked beef [58,59] and fresh Mediterranean fish and shellfish [60]. Toluene exhibited a distinct distribution among Pleurotus volatiles, its concentrations being 3-13 times lower in P. eryngii when compared to P. ostreatus (Figure 1, Tables S1 and S2).…”
Section: Other Compounds-toluenementioning
confidence: 96%
“…Several studies have been reported on the volatile composition of edible freshwater mollusks such as clams [ 12 ], mussels, shrimp and squid [ 13 ]. Sekiwa et al [ 12 ] identified 49 compounds in clams among which were; 2,5-dimethyl-4-hydroxy-3(2H)-furanone, 2-acetyl-2-thiazoline, 2-acetylthiazole and 3-methylthiopropanal.…”
Section: Introductionmentioning
confidence: 99%
“…Sekiwa et al [ 12 ] identified 49 compounds in clams among which were; 2,5-dimethyl-4-hydroxy-3(2H)-furanone, 2-acetyl-2-thiazoline, 2-acetylthiazole and 3-methylthiopropanal. Whereas, Giogios et al [ 13 ], reported high amounts of aldehydes, furans, and N-containing compounds (i.e. pyridine, pyrazines and pyrroline) in mussels.…”
Section: Introductionmentioning
confidence: 99%